2010
DOI: 10.1104/pp.110.160234
|View full text |Cite
|
Sign up to set email alerts
|

WAVY LEAF1, an Ortholog of Arabidopsis HEN1, Regulates Shoot Development by Maintaining MicroRNA and Trans-Acting Small Interfering RNA Accumulation in Rice    

Abstract: In rice (Oryza sativa), trans-acting small interfering RNA (ta-siRNA) is essential for shoot development, including shoot apical meristem (SAM) formation and leaf morphogenesis. The rice wavy leaf1 (waf1) mutant has been identified as an embryonic mutant resembling shoot organization1 (sho1) and sho2, homologs of a loss-of-function mutant of DICER-LIKE4 and a hypomorphic mutant of ARGONAUTE7, respectively, which both act in the ta-siRNA production pathway. About half of the waf1 mutants showed seedling lethali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 45 publications
(61 reference statements)
1
65
0
Order By: Relevance
“…With the tremendous advances in high-throughput sequencing technologies, it is possible systematically to study sRNA population in hen1 mutants with unprecedented depth. Several hen1 mutant alleles have been identified in both Arabidopsis and rice Abe et al, 2010;Yu et al, 2010). In this analysis, we analyzed three hen1 mutant alleles in Arabidopsis, three hen1 alleles in rice, and a newly identified hen1 mutant in maize.…”
Section: Sequencing Of Srnas From Plant Hen1 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the tremendous advances in high-throughput sequencing technologies, it is possible systematically to study sRNA population in hen1 mutants with unprecedented depth. Several hen1 mutant alleles have been identified in both Arabidopsis and rice Abe et al, 2010;Yu et al, 2010). In this analysis, we analyzed three hen1 mutant alleles in Arabidopsis, three hen1 alleles in rice, and a newly identified hen1 mutant in maize.…”
Section: Sequencing Of Srnas From Plant Hen1 Mutantsmentioning
confidence: 99%
“…A family of SMALL RNA DEGRADING NUCLEASE (SDN) proteins was identified in Arabidopsis that degrades mature miRNAs (Ramachandran and Chen, 2008). Work on plant HEN1 has been primarily performed in Arabidopsis, the characterization of wavy leaf1 (waf1) mutants in rice (Oryza sativa), the ortholog of Arabidopsis HEN1 (Abe et al, 2010), and a newly identified hen1 mutant in maize (Zea mays) represent an opportunity to expand our understanding of HEN1 function into monocots. In this study, we used deep sequencing to characterize the extent of 39 modification of sRNAs in both the wild type and hen1 mutants of Arabidopsis, rice, and maize and found that, in contrast with the previous understanding that all miRNAs are simply shortened or tailed in hen1, the pattern of 39 modifications varied substantially among miRNA families, and both truncation and tailing are AGO1 dependent.…”
Section: Introductionmentioning
confidence: 99%
“…HEN1 was first identified genetically as a miRNA biogenesis co-factor, which was shown to localize into the nucleus (Park et al, 2002;Vaucheret et al, 2004;Vazquez et al, 2004). The HEN1 ortholog in rice was identified as WAF (WAVY LEAF), a crucial developmental factor (Abe et al, 2010). Structural analysis of HEN1 and its homologs showed that the catalytic domain of HEN1 is not closely related to any known RNA:2'-OH methyltransferases, but rather to small-molecule methyltransferases (Tkaczuk et al, 2006).…”
Section: Rdr6mentioning
confidence: 99%
“…Whereas HEN1 is also single copy in rice, there are numerous phenotypic differences in the rice hen1 ("waf ") mutants, compared with Arabidopsis, most of which reflect a more severe impact on normal biological functions. For example, rice hen1 mutants show seedling lethality and phenotypes reminiscent of trans-acting siRNA (tasiRNA)-defective mutants in rice (Abe et al 2010). Because mutants in the rice ortholog were identified only recently, work on the plant HEN1 gene has been primarily performed in Arabidopsis; however, the characterization of wavy leaf1 (waf1) mutants represents an opportunity to expand our understanding of HEN1 function in monocots.…”
Section: Discovery Of Hen1 and Its Conserved Function In Many Speciesmentioning
confidence: 99%
“…These include the weaker hen1-2 allele, also from Ler, and the identical point mutation in the Columbia (Col) background isolated from an independent genetic screen and known as hen1-8 (Yu et al 2010); curiously, the same allele in different backgrounds produces different phenotypes, with a more severe developmental impact (on fertility, for example) in the Col background as well as greater molecular effects such as a reduction in miRNA levels (Yu et al 2010). In rice, two mutant alleles in the ortholog WAVY LEAF1 (WAF1) of Arabidopsis HEN1 have been described; the rice waf1-1 and waf1-2 mutants each bear a single-base substitution, leading to a premature stop codon in the second exon and a nonfunctional splicing site of the fourth intron, respectively (Abe et al 2010). Whereas HEN1 is also single copy in rice, there are numerous phenotypic differences in the rice hen1 ("waf ") mutants, compared with Arabidopsis, most of which reflect a more severe impact on normal biological functions.…”
Section: Discovery Of Hen1 and Its Conserved Function In Many Speciesmentioning
confidence: 99%